1981
DOI: 10.1111/j.1468-2958.1981.tb00571.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Consequences of Television-Related Parent-Child Interaction

Abstract: This is a theoretical examination of certain ways in which a child's development may be affected by parentchild interactions in which the content of television programming appears as an explicit referent, i.e., as the topic of a verbal exchange, as the premise for a game, and so forth. The discussion deals with four areas of development, viz.: (1) the child's interpretational skills with regard to the television medium; (2) the child's repertory of cognitive categories regarding the real world; (3) the child's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Although interpersonal communication appears to be limited during the act of watching television (Maccoby, 1951;Walters & Stone, 1971), television can help family members enlarge their repertoire of shared experiences (Holloway & Green, 2008;Silverstone, 1994) and can allow them to argue or illustrate personal points of view during discussions (Lull, 1980a(Lull, , 1980b. Watching television together can help family members to compare and adjust their understandings of and emotional reactions to particular media content (Messaris & Sarett, 1981). Finally, television serves as a means of social comparison for tasks and issues in family members' personal lives.…”
Section: Television Viewing Within the Family As A Starting Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…Although interpersonal communication appears to be limited during the act of watching television (Maccoby, 1951;Walters & Stone, 1971), television can help family members enlarge their repertoire of shared experiences (Holloway & Green, 2008;Silverstone, 1994) and can allow them to argue or illustrate personal points of view during discussions (Lull, 1980a(Lull, , 1980b. Watching television together can help family members to compare and adjust their understandings of and emotional reactions to particular media content (Messaris & Sarett, 1981). Finally, television serves as a means of social comparison for tasks and issues in family members' personal lives.…”
Section: Television Viewing Within the Family As A Starting Pointmentioning
confidence: 99%
“…Television characters and their behaviors provide possible role models that may be discussed and evaluated with respect to family members' own experiences and the family's value system. These models are ultimately accepted or rejected in family decisions (Lull, 1980a(Lull, , 1980bMessaris & Sarett, 1981;Silverstone, 1994).…”
Section: Television Viewing Within the Family As A Starting Pointmentioning
confidence: 99%
“…Research on media consumption at home and audience studies have already demonstrated how and to what extent television stimulates interaction among its users during viewing and among family members in various moments extended over time 268 LETIZIA CARONIA (Lindlof, 1987;Lull, 1990;Morley, 1992;Pasquier, 2001). Through these interactions, children would attribute meaning to the activity of "watching television" and elaborate the television contents in a highly specific manner (Alexander, Ryan, & Munoz, 1984;Messaris, 1982;Messaris & Sarrett, 1981;Weintraub Austin, Roberts, & Nass, 1990). This, however, is just the point: what happens when this activity is situated in the classroom, a very different social and cultural context?…”
Section: The Classroom As a Context For Television Consumptionmentioning
confidence: 99%
“…More recent studies have found that mothers actively attempt to turn television content into messages more appropriate for their children (Messaris & Sarett, 1981;Messaris, 1982). In direct reference to family values, a complex series of studies have found that the more television children watch, the more likely they are to adopt that medium's view of even family behavior-a relationship actually strengthened by everyone of the observed ways that parents attempt to intervene in the process (Buerkel-Rothfuss et al, 1982).…”
Section: Conflict With Other Institutionsmentioning
confidence: 99%